Perbandingan Performa Ayam Broiler dengan Sistem Pemeliharaan Kandang Semi Close House pada Tipe Kandang Bertingkat - Nurvilaeli, Devi; Widianingrum, Dini; Adam Yuliandri, Lili (Tropical Livestock Science Journal, 2025)
This study aims to determine the performance of broiler chickens kept in upper and lower floor cages in a semi-close house system. This study was conducted on January 8 - February 5, 2025 in Burujulkulon Village, Jatiwangi District, Majalengka Regency. The material used in this study was broiler chickens with a population sample (100 chickens/floor). Data analysis used was t-test analysis with 2 treatments and 10 replications. The method used in this study was observation to collect data related to broiler chicken performance. The variables observed were feed consumption (Feed Intake), Body weight gain, ration conversion (FCR), and mortality. The data obtained were analyzed using the independent sample T test. The results of this study indicate that there is no significant difference in feed consumption in the upper and lower floor cages, but there is a significant difference in body weight gain, and feed conversion, the average body weight of the upper and lower floors is 1,649.50 grams/head and 1,534.10 grams/head, with a mortality rate on the upper floor of 3.391%, and the lower floor of 3.533%, the highest FCR value is on the upper floor, which is 1.46, while the lowest value is on the lower floor, which is 1.36. In conclusion, the lower floor cage is better than the upper floor cage for broiler chicken performance.